The Ombudsman of Indonesia’s Own-Initiative Investigations in State Administrative Law and Horizontal Accountability - Riska Jenni Astriani; Jatmiko Yogopriyatno; Nursanty Nursanty (Sharia Faculty, Kiai Haji Achmad Siddiq State Islamic University of Jember, 2026)
Own Initiative Investigation (IAPS) is a constitutional authority of Indonesia's Ombudsman based on Law No. 37/2008 as a proactive public service oversight mechanism. However, its implementation remains low, including in Ombudsman RI Bengkulu Representative which has only conducted 1 IAPS since 2025 despite a 7,1% increase in maladministration cases. This study analyzes IAPS practice from an administrative law perspective as a manifestation of proactive horizontal accountability based on Mark Bovens' theory. Descriptive qualitative research with juridical-empirical approach. Data collected through in-depth interviews with 6 key informants, observations, and legal documentation studies. Analysis uses Miles & Huberman model with Bovens' public accountability framework. IAPS practice in Bengkulu Representative meets formal legality criteria but faces operational constraints in fulfilling Bovens' effective accountability criteria, particularly: (1) Independence constrained by coordination with reported institutions; (2) Transparency limited to LHI publication; (3) Evidence credibility depends on investigator competence; (4) Recommendation consequences weak due to lack of binding sanctions. Juridically, IAPS has strong constitutional legitimacy but its effectiveness is hampered by absence of administrative sanctions for institutions failing to follow up recommendations. IAPS as proactive horizontal accountability instrument requires strengthening of derivative regulations providing stronger binding power to Ombudsman recommendations, including administrative sanctions for non-compliant institutions.